A case report of Graves’ disease following SARS-CoV-2 infection - Rockett, John; Nelson, Colbert; Pierce, Robert; Morlan, Amie Van (International Journal of Contemporary Pediatrics, 2021)
SARS-CoV-2 pandemic has had significant impacts on the world. The longer the pandemic continues the more we learn about the virus behind it and the post-infection complications. SARS-CoV-2 infections have been associated with immune dysfunction and thyroid disease. The spectrum of thyroid disease reported spans from subacute thyroiditis to Hashimoto’s thyroiditis. We report a 16-years-old patient whose COVID-19 infection was followed by multiple complications including the appearance of symptomatic Graves’ disease. Laboratory analysis was significant for elevated TSH, low free thyroxine, and antibodies consistent with the diagnosis of Graves’ disease. This is the first case of Graves’ disease after COVID-19 infection to be reported and the first case of thyroid dysfunction secondary to COVID-19 infection reported in the pediatric population. The spectrum of thyroid and autoimmune disease following COVID-19 is discussed. Further research into the underlying pathology behind COVID-19 infection and immune dysfunction will lead to expediated diagnosis and improved patient outcomes.